Menstrual pain and risk of epithelial ovarian cancer: Results from the Ovarian Cancer Association Consortium. Issue 3 (21st September 2017) - Babic, Ana; Harris, Holly R.; Vitonis, Allison F.; Titus, Linda J.; Jordan, Susan J.; Webb, Penelope M.; ,; Risch, Harvey A.; Rossing, Mary Anne; Doherty, Jennifer A.; Wicklund, Kristine; Goodman, Marc T.; et al.
Abstract : Menstrual pain, a common gynecological condition, has been associated with increased risk of ovarian cancer in some, but not all studies. Furthermore, potential variations in the association between menstrual pain and ovarian cancer by histologic subtype have not been adequately evaluated due to lack of power. We assessed menstrual pain using either direct questions about having experienced menstrual pain, or indirect questions about menstrual pain as indication for use of hormones or medications. We used multivariate logistic regression to calculate the odds ratio (OR) for the association between severe menstrual pain and ovarian cancer, adjusting for potential confounders and multinomial logistic regression to calculate ORs for specific histologic subtypes. We observed no association between ovarian cancer and menstrual pain assessed by indirect questions. Among studies using direct question, severe pain was associated with a small but significant increase in overall risk of ovarian cancer (OR = 1.07, 95% CI: 1.01–1.13), after adjusting for endometriosis and other potential confounders. The association appeared to be more relevant for clear cell (OR = 1.48, 95% CI: 1.10–1.99) and serous borderline (OR = 1.31, 95% CI: 1.05–1.63) subtypes. In this large international pooled analysis of case‐control studies, we observed a small increase in risk of ovarian cancer for women reporting severe menstrual pain. While we observed an increased ovarian cancer risk with severe menstrual pain, the possibility of recall bias and undiagnosed endometriosis cannot be excluded. Future validation in prospective studies with detailed information on endometriosis is needed. Abstract : What's new? Menstrual pain has been associated with increased risk of ovarian cancer in some, but not all studies. This large international pooled analysis of case‐control studies shows a small increase in risk of ovarian cancer for women reporting severe menstrual pain. Since severe menstrual pain is a common condition, even a small increase in risk would translate into a substantial impact on a population level. The possibility of recall bias and undiagnosed endometriosis could however not be excluded, calling for the further examination of this association in prospective studies.